Changes of brain structure in Parkinson's disease patients with mild cognitive impairment analyzed via VBM technology. (29th September 2017) - Gao, Yuyuan; Nie, Kun; Huang, Biao; Mei, Mingjin; Guo, Manli; Xie, Sifen; Huang, Zhiheng; Wang, Limin; Zhao, Jiehao; Zhang, Yuhu; Wang, Lijuan
Highlights: PD cognitive impairment involves extensive cortical and subcortical atrophy. Overall cognitive function in non-dementia PD was mainly located in the frontal and limbic system, and was dominated by subcortical atrophy. PD-MCI is correlated with brain atrophy in local areas such as the frontal lobe, limbic lobe, medial temporal lobe and basal ganglia. The subtle brain structure of the PD early cognitive impairment stage and PD-MCI stage can be detected via VBM technology. Local brain atrophy may be a neuroimaging marker for the early diagnosis of PD-MCI. Abstract: Objective: To analyze changes in cerebral grey matter volume and white matter density in non-dementia Parkinson's disease patients using voxel-based morphometry (VBM) technology; to investigate features of brain structure changes in Parkinson's disease patients with mild cognitive impairment (PD-MCI), and reveal their intrinsic pathological changes. Methods: Based on the diagnostic criteria of PD-MCI, 23 PD-MCI patients, 23 Parkinson's disease patients with normal cognition (PD-NC), and 21 age- and gender-matched healthy people were recruited for the study. Scans were performed on all subjects on a 3.0T MR scanner to obtain brain structural magnetic resonance images. Images were preprocessed using the VBM8 tool from SPM8 software package on the Matlab R2008a platform, and data were then analyzed using the SPM statistical software package to compare the differences of grey matter volume and white matter density between groups, and to evaluate the brain structural changes corresponding to the overall cognitive function. Results: Compared to the control group, the PD-NC group suffered from grey matter atrophy, mainly found in the prefrontal lobe, limbic lobe and left temporal gyrus. The PD-MCI group suffered from grey matter atrophy found in the frontal lobe, limbic lobe, basal ganglia and cerebellum. Compared to the PD-NC group, the PD-MCI group suffered from grey matter atrophy found in the left-side middle temporal gyrus, inferior temporal gyrus and frontal lobe. The grey matter regions correlated with MMSE score (mainly memory related) including the right cingulate gyrus and the limbic lobe. The grey matter regions correlated with MoCA score (mainly non-memory related) including the frontal lobe, basal ganglia, parahippocampal gyrus, occipital lobe and the cerebellum. Additionally, overall cognitive function in non-dementia PD was mainly located in the frontal and limbic system, and was dominated by subcortical atrophy. Conclusion: Structural changes in PD-MCI patients are associated with overall cognitive function, and the atrophic areas are mainly located in the frontal and limbic system, and are dominated by subcortical atrophy. Moreover, atrophy of limbic lobes is associated with impaired memory, whereas frontal lobe atrophy is associated with executive dysfunction. In addition, the subtle brain structure of the PD early cognitive impairment stage and PD-MCI stage can be detected via VBM technology, and thus, local brain atrophy may be a neuroimaging marker for the early diagnosis of PD-MCI.